Information Content of Earnings Announcements: Evidence from After-Hours Trading - Jiang, Christine X.; Likitapiwat, Tanakorn; McInish, Thomas H. (Journal of Financial and Quantitative Analysis, 2012)
Abstract We study after-hours trading (AHT), price contributions, and price discovery following quarterly earnings announcements released outside of the normal trading hours. For Standard & Poor’s (S&P) 500 index stocks from 2004–2008, AHT is heightened on announcement days. A significant portion of the price change and price discovery occurs immediately after the earnings releases. Prices in AHT show a large degree of informational efficiency, further demonstrating the importance of price discovery in AHT. We also provide evidence suggesting that firms prefer after-hours earnings announcements, as trades are mainly from informed traders, and those trades are relied upon to convey information to the general public.